KEWENANGAN DIREKTORAT JENDERAL BEA DAN CUKAI DALAM PEMUNGUTAN BEA MASUK TINDAKAN PENGAMANAN ATAS KAIN IMPOR - Yohanes Pradipta Eka Yudha Adi Nugraha; Hedwig Adianto Mau; Mardi Candra (Journal of Innovation Research and Knowledge, 2025)
The Textile and Textile Products (TPT) industry is one of the vital sectors in international trade for Indonesia. With the issue of increased imported fabrics, the Directorate General of Customs and Excise, which holds the authority under Law Number 17 of 2006 on Amendments to Law Number 10 of 1995 on Customs, is tasked with regulating, supervising, and collecting import duties to protect the domestic industry from the negative impacts of international trade. One of the instruments used is the imposition of Safeguard Import Duties (BMTP), which is applied when a surge in imports of certain goods, such as fabrics, poses a serious threat to the sustainability of the domestic industry. The theories used in this study are the theory of the Pancasila state and the theory of legal certainty. The type of research used in this study is normative legal research utilizing secondary data sourced from library materials, including primary legal materials, secondary legal materials, and tertiary legal materials. In this study, data processing was carried out by systematically organizing legal materials. The research findings indicate that the authority of the Directorate General of Customs and Excise in collecting Safeguard Duty (BMTP) on imported fabrics is in accordance with the provisions of Law Number 10 of 1995 in conjunction with Law Number 17 of 2006 and Minister of Finance Regulation (PMK) Number 48 of 2024. Articles 16 and 17 of Law Number 17 of 2006 on Customs grant customs officials and the Director General of Customs and Excise the authority to determine and collect Import Duty (BM) on imported goods, including BMTP. In the context of imposing BMTP on imported fabrics, customs officials and the Director General of Customs and Excise exercise their functions based on policies established by the Minister of Finance through PMK Number 48 of 2024, as stipulated in Article 23D, paragraph (2) of Law Number 17 of 2006 on Customs. An ideal legal framework for BMTP collection policy on imported fabrics is realized through the principle of legal certainty, as reflected in PMK Number 48 of 2024 and Law Number 10 of 1995 in conjunction with Law Number 17 of 2006. This legal certainty encompasses a clear legal basis, transparent procedures, avoidance of overlapping policies, non-discrimination, and a well-defined objection and appeal mechanism. Furthermore, the implementation of BMTP policy emphasizes information transparency, periodic evaluations, and consistent supervision to enhance public trust in the legal system while maintaining a balance between protecting domestic industries and safeguarding consumer interests.